Literary Internet: Online Criticism and Literary Communication - Winiecka, Elżbieta (Porównania, 2020)
This article is devoted to the transformations that literary communication has undergone on the Internet. The author describes how literary criticism and its role in the digital medium has changed, indicates the deep cultural changes resulting from the development of forms of communication in social media, and characterizes how the Internet has transformed literature. New media has given rise to new literary genres; it has also altered literature itself, recasting it in a hybrid form on the border between the literature and audiovisual media. The ongoing changes do not pose a threat to printed literature, but are an expression of the strength of the Internet’s impact on literary communication and its participants. It is necessary to refrain from easy evaluations of the ongoing processes and to focus on accurately describing, analyzing and interpreting them as a new and relatively unknown part of the expanding literary field.